Effects of pennyroyal (Mentha pulegium L.) dietary supplementation on performance, carcass quality, biochemical parameters and duodenal histomorphology of broilers - ÖLMEZ, M; YÖRÜK, MA (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, the effects of (Mentha pulegium L.) dietary supplementation on performance, carcass characteristics, some biochemical parameters, and intestinal histology were investigated in broiler chickens. Four groups were formed as control and groups treated with pennyroyal at different levels (0.25%, 0.50%, and 1.00%). In the experiment each group had eight replicates. A total of 192 broilers were used in the study with six broilers in each replicate. Water and feed were ad libitum provided. Adding different levels of pennyroyals to broiler rations significantly affected performance parameters; an increase in final body weight and carcass yield and a decrease in total feed intake and the conversion rate was observed (P<0.05). Serum cholesterol, malondialdehyde, and glutathione values were also affected by the addition of pennyroyal (P<0.05). Pennyroyal was effective in vitro against S. enteritidis, E. coli, S. aureus, S. abortus ovis, B.anthracis sterne strains. Besides, it increased the duodenum villus’ length compared to the control group (P<0.05). On the other hand, pennyroyal did not affect carcass and visceral organ weights, several serum biochemical values (P>0.05). As a result, it was concluded that pennyroyal at the level of 0.50% in ration was effective on health and growth performance of broilers.